The struggles behind success: a case study on athletic identity and burnout among university student-athletes in taekwondo - Anjani, Shavilla Adera Nazza; Komarudin, Komarudin; Saputra, Mochamad Yamin; Novian, Geraldi (Jurnal Patriot, 2025)
Problems: Student taekwondo athletes often face challenges balancing academic and sporting roles. The pressure of these two aspects can lead to physical and mental exhaustion or burnout. Burnout that is not properly addressed can impact athletes' performance, motivation, and commitment to sport. Purpose: This study examined the relationship between burnout and athletic identity in taekwondo student-athletes. Methods: A Descriptive method with a quantitative approach was used in this study involving 21 athletes of the UPI Bandung Taekwondo Student Activity Unit. The instruments used in the study were Maslach Burnout Inventory (MBI) and an Athletic Identity Measurement Scale (AIMS) which were given once to the sample. After the data was obtained, data analysis was carried out using the SPSS Version 27. Results: The results showed that there was a significant relationship between athletic identity and burnout among university student-athletes in taekwondo, confirming that athlete identity affects mental and emotional exhaustion. This suggests that athletes who better recognize their role tend to be better able to manage pressure and maintain performance. Conclusion: This study concludes that taekwondo student-athletes have a story of struggle that is not easy behind their success. The relationship between athletic identity and burnout proves the story of struggle.